Antibacterial activity of Synsepalum dulcificum leaf extract against Listeria monocytogenes and its comparison with Strobilanthes crispus and Morus alba (Journal of Bio-Science, 2018)
Abstract not availableJ. bio-sci. 25: 73-75, 2017